Memaafkan Diri dan Kesejahteraan Psikologis: Studi pada Mahasiswa yang Mengalami Kegagalan Akademik - Valensia Teresa; Agustina Agustina; Hanna Christina Uranus (AHKAM, 2026)
Academic failure often generates negative emotions, such as guilt, shame, and disappointment, which in turn diminish students’ psychological well-being. Although this dynamic has received attention in several studies, research specifically examining the role of self-forgiveness in enhancing psychological well-being among students who experience academic failure remains limited. This study aimed to investigate the role of self-forgiveness in improving psychological well-being among university students who had experienced academic failure. A quantitative approach with simple linear regression analysis was employed with 325 students in Jakarta selected through purposive sampling. The instruments used were the self-forgiveness dimension of the Heartland Forgiveness Scale (HFS) and the Psychological Well-Being Scale (PWBS), which was developed based on Ryff’s (1989) six dimensions of psychological well-being. The results showed a significant positive relationship between self-forgiveness and psychological well-being (r = 0.521; p < 0.001), with self-forgiveness contributing 55.7% to psychological well-being, while the remaining 44.3% was influenced by other factors outside the scope of this study. These findings underscore self-forgiveness as an important factor that helps students restore their psychological condition after experiencing academic failure and indicate the need to develop self-forgiveness-oriented strategies to enhance students’ psychological well-being.